(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article is devoted to identifying ways to optimize the process of physical education for students of technical specialties. The purpose of the study was to determine the working conditions and the nature of the labor performed by mechanical engineers, to identify professionally significant psychophysical qualities, to outline the ways of forming physical culture among students of technical specialties, and to determine effective types of motor activity for the successful implementation of this process. The importance of students acquiring a sufficient amount of theoretical knowledge is substantiated, as it forms the basis for developing skills in the proper use of physical culture and sports in work and rest regimes, strengthening health, maintaining high work capacity, and leading a healthy lifestyle. The results of the study confirm the significance of considering the professionogram when planning the process of professional-applied physical training for future mechanical engineers. When compiling a professionogram, it is necessary to create a professionographic description of characteristic working postures, techniques, and working conditions. It was established that a mechanical engineer performs a wide range of functions, including the development and study of technological processes of mechanical processing of parts and machine assembly, as well as the design and operation of metalworking equipment. All these activities require acute vision, precise visual estimation, good hearing, and high tactile and kinesthetic sensitivity. A number of types of motor activity have been identified which, due to their specificity, most effectively contribute to the development of professionally significant psychophysical qualities of future specialists in this field. The characteristic features and specificity of sports games, martial arts, strength, and cyclic sports allow for the effective development of professional psychophysical qualities to the required level.